2020
DOI: 10.1186/s12939-020-01214-3
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting inequalities, gender and adolescent health in Ethiopia

Abstract: Background: Until recently, global public health initiatives have tended to overlook the ways that social factors shape adolescent health, and particularly how these dynamics affect the specific needs of adolescents in relation to information about puberty, menstruation and sexual health. This article draws on mixed methods data from rural and urban areas of Ethiopia to explore how access to health information and resources-and subsequently health outcomes-for adolescents are mediated by gender and age norms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…Adolescence is associated with significant sexual and reproductive health (SRH) vulnerabilities in sub-Saharan Africa (SSA), with long-term consequences and adolescents remain a priority population (Temmerman et al, 2015). Some of these vulnerabilities stem from communities' failure to recognize and protect young people's basic rights by eliminating gender and socioeconomic inequalities and promoting access to services (Jones et al, 2020). Adolescent girls in many countries have high rates of unintended pregnancy, high rates of sexual and gender-based violence (Temmerman et al, 2019) and sexual exploitation (Buller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is associated with significant sexual and reproductive health (SRH) vulnerabilities in sub-Saharan Africa (SSA), with long-term consequences and adolescents remain a priority population (Temmerman et al, 2015). Some of these vulnerabilities stem from communities' failure to recognize and protect young people's basic rights by eliminating gender and socioeconomic inequalities and promoting access to services (Jones et al, 2020). Adolescent girls in many countries have high rates of unintended pregnancy, high rates of sexual and gender-based violence (Temmerman et al, 2019) and sexual exploitation (Buller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is a significant urban–rural variation, with a higher proportion of adolescents living in urban areas having secondary education or higher over the last decade compared to their counterparts in the rural areas. Finally, new means of communication, including the use of social media, are transforming the lives of Ethiopian adolescents, while in this area there are disparities in access and use too [ 7 ].…”
Section: Over the Last Two Decades Political Economic And Social Deve...mentioning
confidence: 99%
“…Other studies on effects of droughts and mental health found out that prolonged drought was associated with increased likelihood of psychological distress, especially in the rural areas (38), and drought related worries especially among the working individuals (39). Similarly, droughts were reported to intensify health outcomes among adolescents in rural Ethiopia (40). On the contrary, (41) reported decrease in health expenditures for households affected with droughts.…”
Section: Multivariate Decomposition Resultsmentioning
confidence: 97%